2017
DOI: 10.12693/aphyspola.131.197
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZrO_2 Addition on the Structure and Dielectric Properties of BaTiO_3 Ceramics

Abstract: Ba(Ti1−xZrx)O3 (x = 0 ÷ 0.3) ceramics were prepared by the standard solid state reaction method and were sintered at 1450• C for 4 h. The structural and dielectric properties of the samples were studied. The phases formed in the ZrO2 doped BaTiO3 were tetragonal and of cubic symmetry. Increase in ZrO2 content in the BaTiO3 caused to increase of the lattice parameter and crystallite size of the perovskite structure. The evolution of the Raman spectra was studied for various compositions and the spectroscopic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In this part additive zirconium oxide ZrO 2 to the barium titanate with two molar ratios (5%, 10%) calcinations at two temperature (950 °C and 1400 °C) then study the structure of barium titanate using x-ray diffraction after this additive, the additives of ZrO 2 to barium titanate lead to change from tetragonal phase to cubic phase at 1400 °C and an increase in lattice parameters [10], this is a clear refers to the addition of Zr lead to disorder in the barium titanate structure [11]. X-ray technique show change in peak position as compared to pure barium titanate.…”
Section: X-ray Diffraction Of Impure Barium Titanate (Bzt)mentioning
confidence: 99%
“…In this part additive zirconium oxide ZrO 2 to the barium titanate with two molar ratios (5%, 10%) calcinations at two temperature (950 °C and 1400 °C) then study the structure of barium titanate using x-ray diffraction after this additive, the additives of ZrO 2 to barium titanate lead to change from tetragonal phase to cubic phase at 1400 °C and an increase in lattice parameters [10], this is a clear refers to the addition of Zr lead to disorder in the barium titanate structure [11]. X-ray technique show change in peak position as compared to pure barium titanate.…”
Section: X-ray Diffraction Of Impure Barium Titanate (Bzt)mentioning
confidence: 99%
“…(Bumajdad et al, 2018;Sigwadi et al, 2019). Also, the high oxidoreductase ability of ZrO 2 allows for the maintenance of enhanced dielectric properties and so can be potential to serve as an insulator in transistors and portable hybrid electronic devices (Daunis et al, 2020;Öksüz et al, 2017. The applications of ZrO 2 can further be enhanced by creating more defective sites for oxygen at its crystal surface and one way to do so is by converting it into a smaller size of several nanometers. In that way, the nanoparticles (NPs) of ZrO 2 are very much suitable particularly for the applications of oxygen and nitrogen gas storage, optical sensors, optoelectronic, dielectric, and bioceramics (Doroshkevich et al, 2022;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey has revealed that the solid-state reaction technique reaction has been used for preparing (Ba 1−x Sr x ) (Zr x Ti 1−x )O 3 and Ba 1-x Sr x ZrO 3 powders. The solid-state reaction is probably one of the most fundamental, practical and routine methods which has been used, developed and modified in both scientific research and industrial mass production for many years [9][10][11][12]. However, a limited study of the synthesis and characterization of Ba 1-x Sr x ZrO 3 (x=0.2, 0.4, 0.6) ceramics by the solid-state reaction has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%